2006
DOI: 10.1017/s0031182006001612
|View full text |Cite
|
Sign up to set email alerts
|

Anti-filarial activity of novel formulations of albendazole against experimental brugian filariasis

Abstract: The study was aimed at developing better orally active albendazole (ALB) formulations. Six formulations (ALB-1 to ALB-6) were prepared and tested against Brugia malayi in Mastomys coucha and jird (Meriones unguiculatus) at 200 mg/kg, orally, for 5 consecutive days. The anti-filarial efficacy was assessed against microfilariae (mf), adult worms and female reproductive potential. Three of the 6 ALB formulations showed greatly improved female worm sterilizing potential (ALB-1: 90%; ALB-3: 63%; ALB-4: 77% of untre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Tissues were teased gently and the parasites recovered were then examined under microscope for status of the motility, cell adherence on their surface, dead or calcified worms [23], [24]. Number of worms recovered from the treated and untreated animals was recorded.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tissues were teased gently and the parasites recovered were then examined under microscope for status of the motility, cell adherence on their surface, dead or calcified worms [23], [24]. Number of worms recovered from the treated and untreated animals was recorded.…”
Section: Methodsmentioning
confidence: 99%
“…All the surviving females were teased individually in a drop of saline to examine condition of intrauterine mf stages of the parasite [23], [24]. Number of sterile female worms recovered from the treated animals was compared with that of control animals and percent sterilization of female worms was determined in treated or control groups over total live female worms recovered from the respective groups.…”
Section: Methodsmentioning
confidence: 99%
“…Different trials were made to use the known drug at its maximum capacity in absence of new drugs. In a study from India, it has been shown that a formulation of albendazole has better anti-filarial efficacy than albendazole itself 17 .…”
Section: Treatment: Medicationmentioning
confidence: 99%
“…[22] Briefly, 8-10 weeks old male jirds were transplanted intraperitoneally (i.p.) with adult worms isolated from the PC of jirds harboring 4-5 months old B. malayi infection.…”
Section: In Vivo Efficacymentioning
confidence: 99%